2015
DOI: 10.1128/cvi.00375-15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Specificity of Two Enzyme Immunoassays for Coccidioidomycosis by Using Sera from a Region of Endemicity and a Region of Nonendemicity

Abstract: b Coccidioidomycosis (CM), a serious life-threatening fungal infection endemic to arid regions of the western United States and Mexico, can be challenging to diagnose in a timely manner. Commercially developed enzyme immunoassays (EIAs) (from Meridian Biosciences and Immuno-Mycologics [IMMY]) have provided faster, simpler means for serodiagnosis; however, independent evaluations have questioned EIA specificity, particularly IgM-positive/IgG-negative results. This study was conducted to evaluate EIA specificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…We demonstrated that a cutoff value of 1.33 EIA units for testing dog sera provided a high degree of sensitivity and specificity that were comparable to the reported rates for the original OMEGA Coccidioides Antibody Enzyme Immunoassay (IMMY) [30]. The assay was also highly specific with minimal signal detected from healthy controls, and animals with confirmed Blastomyces and Histoplasma infections.…”
Section: Discussionsupporting
confidence: 57%
“…We demonstrated that a cutoff value of 1.33 EIA units for testing dog sera provided a high degree of sensitivity and specificity that were comparable to the reported rates for the original OMEGA Coccidioides Antibody Enzyme Immunoassay (IMMY) [30]. The assay was also highly specific with minimal signal detected from healthy controls, and animals with confirmed Blastomyces and Histoplasma infections.…”
Section: Discussionsupporting
confidence: 57%
“…As expected, in our cohort, seroprevalence was higher among patients who lived in highly and established endemic areas, with an observed rate of IgG positivity of 3.7%. This result is similar to previously published rates showing EIA IgG reactivity of 3.6% in a region of endemicity It is of note that among patients who live in suspected endemic areas, we observed a fairly high rate of IgG positivity at 1.3%. Patients residing in suspected endemic areas account for the vast majority of patients who are transplanted at our center.…”
Section: Discussionsupporting
confidence: 92%
“…Serology testing by EIA is the most sensitive method for diagnosis of early coccidioidal infection, however, interpretation of EIA results, particularly isolated IgM in an otherwise asymptomatic patient, can pose difficulty . While isolated IgM antibody in this setting may represent early infection, there are significant rates of false positivity . Repeat testing at a later date can be informative in identifying infection if subsequent seroconversion occurs.…”
Section: Discussionmentioning
confidence: 99%
“…61 Thus, IgM detected by EIA appears to be prone to false-positive results. 64 The sensitivity of EIA IgG is comparable to ID and CF. Another challenge with EIA is that early treatment with fluconazole in those with IgM positivity may lead to lack of seroconversion to IgG.…”
Section: Box 4 My Patient Has a Diffuse Skin Rash Or Eruption Is Thimentioning
confidence: 93%